Reports on the 2015 AAAI Workshop Series - Albrecht, Stefano V.; Beck, J. Christopher; Buckeridge, David L.; Botea, Adi; Caragea, Cornelia; Chi, Chi‐hung; Damoulas, Theodoros; Dilkina, Bistra; Eaton, Eric; Fazli, Pooyan; Ganzfried, Sam; Giles, C. Lee; et al. (The AI magazine, 2015)
AAAI's 2015 Workshop Program was held Sunday and Monday, January 25–26, 2015, at the Hyatt Regency Austin Hotel in Austin, Texas, USA. The AAAI‐15 workshop program included 16 workshops covering a wide range of topics in artificial intelligence. Most workshops were held on a single day. The titles of the workshops included Algorithm Configuration; Artificial Intelligence and Ethics; Artificial Intelligence Applied to Assistive Technologies and Smart Environments; Artificial Intelligence for Cities; Artificial Intelligence for Transportation: Advice, Interactivity, and Actor Modeling; Beyond the Turing Test; Computational Sustainability; Computer Poker and Imperfect Information; Incentive and Trust in E‐Communities; Knowledge, Skill, and Behavior Transfer in Autonomous Robots; Learning for General Competency in Video Games; Multiagent Interaction without Prior Coordination; Planning, Search, and Optimization; Scholarly Big Data: AI Perspectives, Challenges, and Ideas; Trajectory‐Based Behaviour Analytics; and World Wide Web and Public Health Intelligence.